First investigation of the diamagnetic cavity boundary layer with a 1D3V PIC simulation - Beth,A; Gunell,H; Simon,Wedlund C; Goetz,C; Nilsson,H; Hamrin,M (Astronomy and Astrophysics: a European journal, 2022)
Context. Amongst the different features and boundaries encountered around comets, one remains of particular interest to the plasma community: the diamagnetic cavity. Crossed for the first time at 1P/Halley during the Giotto flyby in 1986 and later met more than 700 times by the ESA Rosetta spacecraft around Comet 67P/Churyumov-Gerasimenko, this region, almost free of any magnetic field, surrounds nuclei of active comets. However, previous observations and modelling of this part of the coma have not yet provided a definitive answer as to the origin of such a cavity and on its border, the diamagnetic cavity boundary layer.Aims. We investigate which forces and equilibrium might be at play and balance the magnetic pressure at this boundary down to the spatial and temporal scales of the electrons in the 1D collisionless case. In addition, we scrutinise assumptions made in magneto-hydrodynamic and hybrid simulations of this environment and check for their validity.Methods. We simulated this region at the electron scale by means of 1D3V particle-in-cell simulations and SMILEI code.Results. Across this layer, depending on the magnetic field strength, the electric field is governed by different equilibria, with a thin double-layer forming ahead. In addition, we show that the electron distribution function departs from Maxwellian and/or gyrotropic distributions and that electrons do not behave adiabatically. We demonstrate the need to investigate this region at the electron scale in depth with fully kinetic simulations.